Application of Multifunctional Metal Nanoparticles in the Treatment of Glioma - Ren Y; Yang H; Xu D; Zhang Z; Gao S; Yu R (International Journal of Nanomedicine)
Yanhong Ren,1,2,* Han Yang,3,* Duo Xu,4 Zhengkui Zhang,4 Shangfeng Gao,1,4 Rutong Yu1,4 1Department of Neurosurgery, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, 221002, People’s Republic of China; 2Beijing Institute of Brain Disorders, Capital Medical University, Beijing, 100069, People’s Republic of China; 3Department of Neurology, The First Hospital of Changsha, Changsha, 410008, People’s Republic of China; 4Institute of Nervous System Diseases, Xuzhou Medical University, Xuzhou, Jiangsu, 221002, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shangfeng Gao; Rutong Yu, Email gaoshangfeng@xzhmu.edu.cn; rtyu@xzhmu.edu.cnAbstract: Glioma is the most common primary malignant brain tumor with a poor survival rate. It is characterized by diffuse and invasive growth and heterogeneity, which limits tumor identification and complete resection. Therefore, the precise detection and postoperative adjuvant therapy of gliomas have become increasingly important and urgent. Nanotechnology, with its excellent biocompatibility and controllable chemical properties, has attracted much attention in recent decades. Metal nanoparticles are widely used in the field of biomedical imaging and detection, and have shown promising applications in targeted drug delivery and therapy. The current review aims to systematically summarize the application of different types of metal nanoparticles in the treatment and detection of glioma. We also discussed the advantages and mechanisms of metal nanoparticles when used for glioma therapy, including chemotherapy, radiotherapy and photothermal therapy. We hope to promote the application of metallic nanoparticles in glioma diagnosis and treatment, moving towards clinical translation to benefit patients.Keywords: metal nanoparticles, glioma, treatment